Multi‐informant International Perspectives on the Facilitators and Barriers to Employment for Autistic Adults. Issue 7 (14th March 2020) - Black, Melissa H.; Mahdi, Soheil; Milbourn, Benjamin; Scott, Melissa; Gerber, Alan; Esposito, Christopher; Falkmer, Marita; Lerner, Matthew D.; Halladay, Alycia; Ström, Eva; D'Angelo, Axel; Falkmer, Torbjorn; et al.
Abstract: Employment rates for autistic individuals are poor, even compared to those from other disability groups. Internationally, there remains limited understanding of the factors influencing employment across the stages of preparing for, gaining, and maintaining employment. This is the third in a series of studies conducted as part of an International Society for Autism Research (INSAR) policy brief intended to improve employment outcomes for autistic individuals. A multi‐informant international survey with five key stakeholder groups, including autistic individuals, their families, employers, service providers, and researchers, was undertaken in Australia, Sweden, and the United States to understand the facilitators and barriers to employment for autistic adults. A total of 687 individuals participated, including autistic individuals ( n = 246), family members ( n = 233), employers ( n = 35), clinicians/service providers ( n = 123), and researchers ( n = 50). Perceptions of the facilitators and barriers to employment differed significantly across both key stakeholder groups and countries, however, ensuring a good job match and focusing on strengths were identified by all groups as important for success. Key barriers to employment included stigma, a lack of understanding of autism spectrum disorder (ASD) and communication difficulties. Results suggest that a holistic approach to employment for autistic individuals is required, aimed at facilitating communication between key stakeholders, addressing attitudes and understanding of ASD in the workplace, using strength‐based approaches and providing early work experience. Autism Res 2020, 13 : 1195‐1214. © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Autistic individuals experience significant difficulty getting and keeping a job. This article presents a survey study involving autistic individuals, their families, employers, service providers and researchers in Australia, Sweden, and the United States to understand their perspectives on the factors that support or act as barriers to employment. While perspectives varied across key stakeholders, strategies such as using a holistic approach, targeting workplace attitudes and understanding, focusing on strengths, and providing early work experience are important for success.